Improving neonatal care with the help of veteran resource parents: An overview of current practices. Issue 1 (February 2018) - Bourque, Claude Julie; Dahan, Sonia; Mantha, Ginette; Robson, Kate; Reichherzer, Martin; Janvier, Annie
Abstract: Over the past decade, veteran parents who have lived a neonatal intensive care unit (NICU) experience have become increasingly involved as 'resource parents' to provide peer-to-peer support to "new" NICU parents. These parents can provide a unique form of support to new parents. They can also assume other roles in clinical care, research, administration and/or teaching, but those roles are rarely described in the literature. This article reviews many of the activities performed by resource parents in neonatology. These activities were identified/examined and classified according to the location of involvement (hospital or not), the presence/absence of direct interaction with families and providers, and the topic of involvement. We have also identified gaps in knowledge relative to recruitment and training, development and evaluation of programs, structuring of responsibilities, and remuneration of resource parents. Future research is needed to measure the impact of resource parents on neonatal care.